Observer-based improved Composite Nonlinear Feedback control for output tracking of time-varying references in descriptor systems with actuator saturation. (August 2019) - Jafari, E.; Binazadeh, T.
Abstract: In this paper, an observer-based improved Composite Nonlinear Feedback (CNF) controller is proposed for output tracking of general time-varying reference signals in descriptor systems subject to actuator saturation. Different parts of the proposed control law are designed based on the reconstructed states by a full-order descriptor observer. Algebraic constraints in descriptor systems can significantly complicate design procedures of the observer and the controller. Moreover, considering the actuator saturation constraint, adds additional complexity to the tracking problem. On the other hand, the proposed improved CNF controller's performance is also challenged in presence of external disturbances. The effect of external disturbances, along with the previous mentioned constraints, needs extremely intricate calculations for investigating the solvability of the tracking problem. Furthermore, due to the nonlinearity of the closed-loop system, steady-state analysis is also needed to show the uniformly ultimately boundedness of the tracking error in presence of external disturbances. In this regard, precise mathematical operations are performed through a theorem, which investigates the tracking goal for three different cases of the saturation function. Finally, the theoretical achievements are verified by computer simulations through numerical and practical examples. Highlights: Time-varying reference tracking in descriptor systems with actuator saturation. Producing arbitrary reference signals by a descriptor reference generator. Proposing an observer-based composite nonlinear feedback controller. Ultimate boundedness analyzing and achieving disturbance attenuation. Proving the solvability of the problem for different cases of saturation function.